Factoring perspective: Croatia vs European Union - Suzana Baresa; Sinisa Bogdan; Zoran Ivanovic (UTMS Journal of Economics, 2012)
This paper points out the problems of liquidity, disposal and obtaining funds, inability to collect receivables, delayed payments in times of economic and financial instability and dynamic business upheavals and uncertainty. As a contribution to resolve these issues new alternative methods of financing for business are imposing, one of them is factoring. Although most countries don't have adequate legal framework, factoring has emerged as the dominant form of financing, whose current status and development points to the prospects of development in the future. In terms of measures and actions which are taken to combat these issues, as well as legislation, many efforts are made at international level in European Union and in Croatia. Overview and description of the factoring development, and indications for further development are presented in relation to the world, the European Union and the Republic of Croatia. This paper also describes factoring comparison among European countries.
Keywords: G32; G33; G35; O52; 330; factoring; liquidity; delayed payments; Republic Croatia; European Union; receivables